Organic Fertilizer Quality Derived from A Combination of Cow Feces and Empty Fruit Bunche Waste - Pancapalaga, Wehandaka; Adiyastiti, Bayu Etty Tri; Rahayu, Imbang Dwi (Universitas Djuanda, 2024)
To address the accumulation of solid waste from empty oil palm fruit bunches and beef cattle farming waste, handling efforts were undertaken, one of which involved utilizing recycling technology to convert solid waste into high-value organic fertilizer products. This study aimed to assess the quality of organic fertilizer derived from a blend of cow feces and empty fruit bunches (EFB) at various proportions. The materials employed encompassed beef cattle feces and empty fruit bunches (EFB) waste. Employing a completely randomized design (CRD), the study encompassed three treatments: P1 (40% cow feces with 60% EFB), P2 (50% cow feces with 50% EFB), and P3 (60% cow feces with 40% EFB). The quality of the compost measured includes levels of Nitrogen (N), Phosphorus (P2O5), Potassium (K2O), Carbon (C-organic), C/N ratio, and moisture content. Research findings indicated that the quality of organic fertilizer resulting from varied ratios of cow feces and EFB insignificantly influences (p>0.05) Potassium, Phosphorus and C-Organic Conversely, it exhibited a significant impact (p<0.05) on Nitrogen content, moisture content, and the C/N ratio. The average values for organic fertilizer were 0.29% for Potassium, 0.23% for Phosphorus, 31.49% for organic Carbon, 1.80% for Nitrogen, and 42.30% for moisture content. The C/N ratio of the organic fertilizer was determined to be 17.87. In conclusion, organic fertilizer derived from a combination of EFB and cow feces complies with the Indonesian National Standard (SNI 19-7030-2004). The optimal ratio for utilizing EFB and cow feces in organic fertilizer production was determined to be 1:1.